Method for depositing porous carbon film through laser-induced plasma and application
By using femtosecond laser-induced plasma depositing of porous carbon films in laser-induced carbonization technology, the problem of difficulty in transfer of carbon materials is solved, and the deposition of high-quality porous carbon films is achieved, which significantly improves its adhesion and conductivity. It is suitable for large-scale production and energy storage applications of supercapacitors.
Patent Information
- Application Number
- CN202411469638.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-04-08
AI Technical Summary
Existing laser-induced carbonization technologies are difficult to transfer the induced carbon materials to other substrates with high efficiency and high quality, resulting in poor stability and practicality of carbon-based electronic components.
A femtosecond laser-induced plasma depositing of porous carbon film is used to set a gap between the substrate and the polyimide film, and a porous carbon film is deposited on the lower surface of the substrate by femtosecond laser scanning to improve its adhesion and robustness.
It significantly improves the adhesion and conductivity of porous carbon materials, simplifies the process, is suitable for large-scale preparation, and improves the electrochemical performance and cyclic stability of planar micro-supercapacitors.
Smart Images

Figure CN119776765A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of femtosecond laser micro-nano processing, and in particular to a method and application of laser-induced plasma deposition of a porous carbon film. Background Art
[0002] Porous carbon materials have shown great application prospects in the fields of energy storage and conversion, catalysis, adsorption separation, photothermal conversion, etc. due to their high specific surface area and rich physical properties. Laser-induced carbonization, as an emerging technology for preparing porous carbon materials, perfectly combines carbonization process and micro-nano processing, which is very conducive to the flexible design and manufacturing of micro carbon-based devices. In recent years, research on the preparation of extraordinary functional devices based on laser-induced carbonization technology has emerged in an endless stream and has shown excellent performance. However, most of the current laser-induced carbonization technologies are to prepare patterned two-dimensional planar carbon structures on polymers by scanning and scribing. However, this technical method has an irreconcilable common problem during laser-induced carbonization, that is, it is difficult to transfer the induced carbon material from the polymer master as a precursor to other substrates.
[0003] In order to solve the above problems, the transfer of carbon materials is realized during laser-induced carbonization. The first method is a two-step transfer method that combines laser-induced carbonization and a transfer process, and the second method is a one-step transfer method based on laser-assisted transfer. Although the first two-step transfer method can transfer patterned carbon materials to other substrates, the process is complicated and requires additional consumables, which is not conducive to the large-scale production of carbon-based electronic components. Although the second one-step transfer method can efficiently realize the transfer of carbon materials to transparent substrates, due to the poor adhesion and robustness of the carbon film after transfer, the prepared carbon-based electronic components have poor stability and extremely poor practicality. Therefore, how to achieve efficient transfer of carbon materials to substrates while ensuring that the process is relatively simple and does not require additional consumables, and the transferred carbon film has good adhesion and robustness, has become an important research direction in the current preparation process of materials such as porous carbon films. Summary of the invention
[0004] The present invention provides a method and application of laser-induced plasma deposition of porous carbon film. When a porous carbon film is deposited on a substrate surface using a femtosecond laser, a certain gap is retained between the substrate and the polyimide film, which can solve the problem of high efficiency and high quality transfer of laser-induced porous carbon materials in the prior art, significantly improve the adhesion of porous carbon materials, and also have good hydrophilicity and electrical conductivity; the entire preparation process is simple and controllable, with high repeatability, and is suitable for mass production. It is specifically achieved through the following technologies.
[0005] A method for laser-induced plasma deposition of a porous carbon film comprises the following steps:
[0006] The carrier, the polyimide film and the substrate are overlapped from bottom to top to form a sandwich structure; a gap is provided between the polyimide film and the substrate, and the width of the gap is 10-25 μm;
[0007] The pattern of the carbon electrode is designed in advance, the sandwich structure is fixed on a stage, and femtosecond laser scanning is performed according to the pattern of the carbon electrode to deposit the porous carbon film on the lower surface of the substrate; the scanning speed is 1-5 mm / s, the scanning interval is the same as the diameter of the femtosecond laser spot irradiated on the polyimide film, and the pattern of the porous carbon film corresponds to the shape of the carbon electrode.
[0008] Optionally, other parameters of the femtosecond laser can be adjusted as follows: wavelength 1028 nm, pulse width 190 fs, repetition frequency 200 kHz, and objective lens magnification for focusing the femtosecond laser is 5 times.
[0009] Furthermore, the gap is arranged in such a manner that two gaskets are provided between the polyimide film and the substrate, the two gaskets are symmetrically arranged on both sides of the to-be-deposited area of the substrate, and the thickness of the gaskets corresponds to the width of the gap.
[0010] Furthermore, the laser scanning speed is 5 mm / s, and the scanning interval is 10 μm, that is, the diameter of the femtosecond laser spot irradiated on the polyimide film is also about 10 μm.
[0011] Furthermore, the substrate is a silicate glass substrate with a transmittance of 85%.
[0012] Furthermore, the carbon electrodes are interdigitated electrodes, the effective length of the interdigitated electrodes is 7 mm, the width is 1 mm, and the number is 5 pairs.
[0013] The present invention also provides a method for assembling a planar micro supercapacitor, which comprises depositing the porous carbon film on the lower surface of the substrate by any of the above methods for depositing a porous carbon film; preparing an electrolyte and a current collector, and encapsulating the electrolyte and the current collector to obtain the planar micro supercapacitor.
[0014] Furthermore, in the assembling method of the planar micro supercapacitor, the electrolyte is a H3PO4-PVA gel electrolyte.
[0015] Furthermore, in the method for assembling a planar micro-supercapacitor, a flexible copper tape and a conductive silver paste are used to assemble the current collector.
[0016] Compared with the prior art, the present invention is beneficial in that:
[0017] 1. The present invention uses femtosecond laser induced plasma deposition to prepare a porous carbon film, and finally forms a super-strong adhesion conductive porous carbon film on the surface of a glass substrate. The porous carbon film prepared by this method has low surface roughness and rich internal microporous structure, and also has good hydrophilicity, conductivity, and excellent adhesion. The thickness of the porous carbon film finally deposited can reach tens of microns.
[0018] 2. This method is simple and flexible to operate, has high precision, non-contact processing and can be prepared in batches.
[0019] 3. The assembled planar micro supercapacitor has excellent electrochemical properties and cycle stability, and has shown wide application in the field of energy storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a diagram of the preparation process of porous carbon film.
[0021] Figure 2 This is an optical photograph of the porous carbon film prepared in Example 1 ( Figure 2 a) and 3D contour plot ( Figure 2 b).
[0022] Figure 3 These are scanning electron microscope (SEM) images of the surface of the porous carbon film prepared in Example 1 at different magnifications.
[0023] Figure 4 This is the energy dispersive spectrometer (EDS) of the porous carbon film prepared in Example 1.
[0024] Figure 5 This is the X-ray diffraction pattern (XRD) of the porous carbon film prepared in Example 1.
[0025] Figure 6 This is the Raman spectrum of the porous carbon film prepared in Example 1.
[0026] Figure 7 This is the transmission spectrum of the porous carbon film prepared in Example 1.
[0027] Figure 8 This is a current-voltage (IV) curve of the porous carbon film prepared in Example 1.
[0028] Fig. 9 Schematic diagram of the contact angle of the porous carbon film prepared in Example 1.
[0029] Fig.10 Adhesion test of the porous carbon film prepared in Example 1 and scanning electron microscope (SEM) images before and after ultrasonic cycle cleaning.
[0030] Fig.11This is a transmission spectrum of the porous carbon film prepared in Example 1 before and after adhesion testing and ultrasonic cycle cleaning.
[0031] Fig.12 Relative resistance change of the porous carbon film prepared in Example 1 before and after adhesion test and ultrasonic cycle cleaning.
[0032] Fig.13 Optical photos of the porous carbon film prepared in Example 1 before and after the tensile test ( Fig.13 a) and force-time curve ( Fig.13 b).
[0033] Fig.14 This is the effect of different gap widths on the porous carbon film in Experimental Example 1.
[0034] Fig.15 This is the effect of different laser powers on the porous carbon film in Experimental Example 1.
[0035] Fig.16 This is the effect of different scanning intervals on the porous carbon film in Experimental Example 1.
[0036] Fig.17 It is an interdigitated porous carbon film ( Fig.17 a) and planar supercapacitors ( Fig.17 b) Photos of the actual object.
[0037] Fig.18 Cyclic voltammetry (CV) curve of interdigitated planar supercapacitor ( Fig.18 a) and constant current charge and discharge (GCD) curves ( Fig.18 b).
[0038] Fig.19 The figure shows the cyclic stability performance of the interdigitated planar supercapacitor under 1000 cycles of constant current charge and discharge. DETAILED DESCRIPTION
[0039] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] In some embodiments of the present invention, a method of depositing a porous carbon film using laser-induced plasma is used, such as Figure 1 As shown, the steps are:
[0041] The carrier (i.e., glass slide), the polyimide film, and the substrate are overlapped from bottom to top to form a sandwich structure; a gap is provided between the polyimide film and the substrate, and the width of the gap is 25 μm; the power of the femtosecond laser is adjusted to 500-700 mW;
[0042] The pattern of the carbon electrode is designed in advance, the sandwich structure is fixed on a stage, and femtosecond laser scanning is performed according to the pattern of the carbon electrode to deposit the porous carbon film on the lower surface of the substrate; the scanning speed is 5 mm / s, the scanning interval is 10 μm, and the pattern of the porous carbon film corresponds to the shape of the carbon electrode.
[0043] In some implementation cases of the present invention, Figure 1 As shown, the setting mode of the gap in the above method can be selected as follows: two gaskets are provided between the polyimide film and the substrate, the two gaskets are symmetrically arranged on both sides of the to-be-deposited area of the substrate, and the thickness of the gaskets corresponds to the width of the gap.
[0044] By adjusting the magnification of the objective lens, the spot size of the femtosecond laser can be adjusted, thereby achieving fine processing of holey carbon films of different scales and pattern shapes.
[0045] Optionally, other parameters of the femtosecond laser can be adjusted to a femtosecond laser with a wavelength of 1028 nm, a pulse width of 190 fs, and a repetition frequency of 200 kHz, and the objective lens magnification for focusing the femtosecond laser is 5 times.
[0046] Optionally, the substrate may be made of a material such as silicate glass having a transmittance of 85%.
[0047] Optionally, the gasket may be a polyimide gasket with a thickness of 25 μm.
[0048] The actual photo of the final prepared porous carbon film is as follows Figure 2 The present invention can also pre-design the pattern shape of the carbon electrode so as to finally deposit a porous carbon film with a corresponding pattern shape on the substrate surface.
[0049] In some embodiments of the present invention, the porous carbon electrode may be designed to be in an interdigitated shape.
[0050] Example
[0051] The method for laser induced plasma deposition of porous carbon film provided in this embodiment comprises the following specific steps:
[0052] 1. Construct a sandwich structure of glass substrate-polyimide precursor-carrier.
[0053] (1) Place the precursor material polyimide film (PI, film thickness 100 μm) and glass substrate (1 mm silicate glass) in a culture dish, and ultrasonically clean them with deionized water and anhydrous ethanol for 20 min respectively. Place the cleaned glass substrate directly above the polyimide film. Figure 1 As shown in the figure, two polyimide spacers (thickness 25 μm) are symmetrically inserted between the glass substrate and the polyimide film. The purpose of the spacers is to create a gap between the glass substrate and the polyimide film. The area between the two polyimide spacers is used to deposit the holey carbon film.
[0054] (2) Place a clean glass slide (carrier) directly underneath the polyimide film to form a glass substrate-polyimide precursor-carrier sandwich structure.
[0055] 2. Deposition preparation of porous carbon film:
[0056] (1) In order to quickly and effectively focus the femtosecond laser on the surface of the polyimide film, a 5x magnification objective lens is also equipped, which reduces the diameter of the femtosecond laser spot to about 10 μm, enabling fine processing of different scales. During the femtosecond laser processing, a CCD camera is equipped to perform real-time imaging of the sample placed on the electric stage for easy observation.
[0057] The parameters of the debugged femtosecond laser are a wavelength of 1028 nm, a pulse width of 190 fs, a repetition rate of 200 kHz, and an average power of 500 mW.
[0058] (2) Place the sandwich structure on the electric stage for femtosecond laser processing and turn on the vacuum pump of the electric stage to firmly fix the sandwich structure.
[0059] The polyimide film was scanned back and forth using a debugged femtosecond laser, with the scanning speed controlled at 5 mm / s and the scanning spacing controlled at 10 μm; finally, the porous carbon film was deposited on the lower surface of the glass substrate.
[0060] 3. Use white light interferometry profilometer and scanning electron microscope to test and characterize the film thickness and film morphology.
[0061] like Figure 2 As shown in a, the porous carbon film on the base surface is dark black and is evenly deposited on the lower surface of the glass substrate. Figure 2 As shown in b, the surface roughness is 0.714 μm. Figure 3 From the SEM image of the porous carbon film, it can be seen that the porous carbon film prepared by this method has a good surface morphology and a porous structure inside. The interface between the porous carbon film and the glass substrate is composed of wavy microchannels. Figure 4From the EDS of the porous carbon film, it can be seen that the main element of the porous carbon film is carbon, and there is a clear boundary between the porous carbon film and the glass substrate. Figure 5 The XRD of the porous carbon film shows that the deposited carbon film is mainly composed of amorphous carbon and graphite. Figure 6 The Raman spectrum also shows that the chemical composition of the porous carbon film is mainly amorphous carbon and graphite.
[0062] Figure 2 The physical properties of the porous carbon film prepared in this example are shown. Compared with the glass substrate without the porous carbon film, the area where the porous carbon film is deposited has higher light absorption capacity and lower transmittance ( Figure 7 ). The conductivity measurement results show that the resistivity of the porous carbon film is 3.1×10 -3 Ωm, has good electrical conductivity ( Figure 8 The porous carbon film exhibits strong hydrophilicity, with a contact angle of less than 10° ( Fig. 9 ), which is beneficial to the penetration of aqueous electrolyte and increases the adsorption of ions.
[0063] 4. The adhesion and stability of the porous carbon film prepared in this example were tested
[0064] First, the adhesion of the porous carbon film under a constant tensile force of 1.25 N / cm was measured using a standard 3M SCOTCH stationery tape. Then, the samples were immersed in anhydrous ethanol and deionized water, respectively, and cyclic ultrasonic cleaning was performed at a vibration frequency of 50 kHz for 30 min to evaluate the film's anti-removal ability; the surface morphology of the porous carbon film after the adhesion test was observed by scanning electron microscopy; then, the transmittance and relative resistance of the porous carbon film were tested to indirectly evaluate its adhesion and stability; finally, the force required for the porous carbon film to be completely peeled off from the glass substrate, i.e., the adhesion of the porous carbon film, was tested by the tensile method on a universal material testing machine at a tensile speed of 0.1 mm / min.
[0065] like Fig.10 From the SEM images, it can be seen that after the tape test, except for the removal of the debris on the surface of the porous carbon film, there is no obvious change in the porous carbon film embedded in the glass substrate; after the cyclic ultrasonic cleaning, the residual adhesive from the tape is removed and a clearer morphology of the porous carbon film can be observed, with a regular and flat morphology. There is no obvious change in the optical morphology of the porous carbon film before and after the adhesion test.
[0066] like Fig.11 and 12 As shown in the figure, after 100 tape stripping tests and 30 min ultrasonic cleaning, the transmittance of the porous carbon film is still maintained below 2%, and the relative change in resistance is less than 1%. This shows that the porous carbon film deposited and prepared in this example has excellent adhesion and stability.
[0067] like Fig.13 The optical photos of the porous carbon film before and after stretching shown in a show that the porous carbon film is completely peeled off from the substrate after the test. Fig.13 From the force-time curve shown in (b), it can be observed that the stress drops sharply when the load is 122 N, which corresponds to the force required to completely separate the porous carbon film from the substrate. It can be seen that the adhesion force of the porous carbon film is as high as 122 N. The excellent adhesion of the porous carbon film comes from the fact that the microchannels greatly increase the contact area between the carbon film and the glass substrate, and the induced carbon-glass recast layer (microchannels) acts as an adhesive to tightly combine the two.
[0068] It can be seen that the porous carbon film deposited on the substrate by the method of this embodiment has good electrical conductivity and hydrophilicity, as well as excellent stability, and the structure can be fully utilized in supercapacitors.
[0069] Experimental Example 1: Effect of different gap widths between glass substrate and polyimide film on the deposition of porous carbon film
[0070] This experimental example designed three groups of control group experiments. The difference between the laser induced plasma deposition method of porous carbon film in the three control groups and the above-mentioned embodiment is that: the first group did not set any gasket between the glass substrate and the polyimide film, or other structures that create a gap between the glass substrate and the polyimide film, that is, the glass substrate and the polyimide film were tightly fitted; the thickness of the Kapton gasket set between the glass substrate and the polyimide film of the second group was 25 μm, that is, the gap width between the glass substrate and the polyimide film was 25 μm. The thickness of the gasket set between the glass substrate and the polyimide film of the third group was 50 μm, that is, the gap width between the glass substrate and the polyimide film was 50 μm.
[0071] The results are as follows Fig.14 As shown in a, it can be seen from the figure that when the glass substrate is in close contact with the polyimide film (i.e., L=0 μm), the high peak power laser pulse acts on the upper surface of the polyimide while also acting on the lower surface of the glass substrate, so that both the polyimide and the glass can absorb the laser energy through multi-photon absorption and be ablated. At the same time, the plasma plumes induced by both parties are confined in a small space, causing the substrate to be continuously bombarded by plasma and ablation particles. The resulting stress will induce a large number of cracks in the substrate, and eventually form a broken sheet structure. The carbon film deposited at this spacing is composed of a large number of ablation particles, with no obvious boundary between it and the glass substrate, and the interface is extremely irregular. A large hole structure can be observed on the glass substrate. There are a large number of cracks on the surface of the carbon film. When the cracks are intertwined, it is easy to form a sheet structure, and the entire film appears damaged.
[0072] like Fig.14 As shown in Figure b, when a spacer of appropriate thickness (L=25 μm) is introduced, since the laser is only focused on the upper surface of the polyimide, it is in a defocused state with respect to the lower surface of the glass substrate, thus only inducing ablation of the polyimide, and the glass substrate is only subjected to laser-induced plasma ablation and heating, resulting in molten microchannels on the surface of the substrate and small holes inside. The laser-ablated carbon particles diffuse backward and combine with the molten microchannels to form a carbon-glass recast layer at the bottom of the microchannel, which greatly enhances the bonding ability of the carbon particles and the glass. The strong bonding force can peel off the porous carbon structure induced by the thermal accumulation effect from the polyimide, thereby obtaining a carbon film with a dense surface and porous interior.
[0073] like Fig.14 As shown in Figure 3, when the spacing is too large (L = 50 μm), the laser-induced plasma is not enough to ablate the glass substrate. Due to gravity, only the lighter laser-ablated carbon particles have enough kinetic potential energy to be converted into gravitational potential energy and adsorbed on the lower surface of the substrate. Therefore, it can be observed that there is a clear boundary between the deposited carbon film and the glass substrate. The glass is not affected and shows a complete morphology. The deposited carbon film is loose and can be easily removed by simple physical adsorption.
[0074] Experimental Example 2: Effect of different laser powers on the deposition of porous carbon films
[0075] The preparation method of the above embodiment was adopted, and the power of the femtosecond laser was adjusted to 400 mW, 500 mW, 600 mW, 700 mW, 800 mW and 900 mW, respectively, and the morphologies of the prepared carbon films were observed respectively.
[0076] The results are as follows Fig.15 As shown in Figure a, when the laser power is 400 mW, the deposited carbon film presents an irregular morphology. This is mainly because the laser power is low at this time, making it difficult for polyimide to absorb enough laser energy to induce carbonization products, and therefore the induced carbon particles are difficult to be uniformly deposited on the surface of the glass substrate.
[0077] like Fig.15 As shown in bd, when the laser power is between 500-700 mW, the surface of the deposited holey carbon film is smooth and dense.
[0078] like Fig.15 As shown in Figure ef, when the laser power is greater than 800 mW, the surface of the deposited carbon film is damaged. This is because the laser power is too high at this time, and the glass substrate can also absorb enough laser energy to be ablated, thus generating cracks.
[0079] Experimental Example 3: Effect of different scanning spacing on the deposition of porous carbon films
[0080] The preparation method of Example 1 was used, and the scanning interval of the femtosecond laser was adjusted to 50 μm, 40 μm, 30 μm, 20 μm and 10 μm, respectively, and the morphology of the prepared carbon film was observed. The results are shown in FIG. Fig.16 As shown, only when the scanning spacing is 10 μm can a continuous and uniform porous carbon film be formed, which means that the scanning spacing must be consistent with the laser spot size to achieve effective deposition of the carbon film on the glass substrate.
[0081] Application Example: Performance Test of Planar Micro-Supercapacitors Assembled Using the Method of Example 1
[0082] 1. Preparation of planar micro supercapacitors
[0083] The method of Example 1 is used to pre-design the pattern shape of the interdigitated porous carbon electrode, and then the corresponding porous carbon film is deposited to obtain the corresponding interdigitated porous carbon electrode, such as Fig.17 As shown in a, the effective length of the interdigital electrodes is 7 mm, the width is 5 mm, and the number is 5 pairs.
[0084] After the deposition of the porous carbon film is completed, it is further assembled into a planar micro supercapacitor.
[0085] As a specific implementation case of the present invention, this application example selects 1 mol / L H3PO4-PVA gel material as the electrolyte, and uses flexible copper tape and conductive silver paste for current collector assembly.
[0086] The specific assembly method is as follows: (1) Prepare 1 mol / L H3PO4-PVA gel electrolyte, and use a rubber-tipped dropper to evenly coat the H3PO4-PVA gel electrolyte on the interdigitated porous carbon electrode; (2) Use a 50 μm thick flexible copper tape and conductive silver paste for current collector assembly, and place the supercapacitor coated with the electrolyte in a 25 ℃ constant temperature drying cabinet for 12 h; (3) Use a 10 μm thick PET film to encapsulate the supercapacitor to obtain a planar solid-state supercapacitor product, such as Fig.17 As shown in b.
[0087] 2. Performance test of planar micro supercapacitor
[0088] When the voltage range is 0-0.8 V, the cyclic voltammetry (CV) curves of the planar micro-supercapacitor at different voltage scan rates are shown in Figure 2. Fig.18 As shown in a. It can be seen that the CV curve is close to a rectangle, indicating that it has typical double-layer capacitance behavior. As the voltage scan rate increases, the specific capacitance gradually decreases, and the maximum value is 0.24 mF / cm at a voltage scan rate of 100 mV / s.2 This may be due to the reduced diffusion of ions in the porous structure and insufficient contact with the interdigitated porous carbon electrode at higher voltage scan rates.
[0089] It can be seen that the specific capacitance of the supercapacitor prepared by laser induced plasma deposition of the present invention is 0.08 mF / cm2, which is higher than the specific capacitance of the supercapacitor prepared by laser assisted transfer (literature "In situ growth of laser-induced graphene micro-patterns on arbitrary substrates", Ednan Joanni, Rajesh Kumar, Willians. P. Fernandes, Raluca Savud and Atsunori Matsuda; The Royal Society of Chemistry; Nanoscale, 2022, 14, 8914–8918). 2 3 times.
[0090] like Fig.18 As shown in Fig. 2b, the GCD curve of the planar micro supercapacitor assembled by the present invention is approximately triangular at a constant current of 10 μA-50 μA. This further confirms the effective deposition of ions at the interface between the electrolyte and the electrode. When charging to the top, the slope of the curve decreases, which is due to the instability of the electrolyte and the transfer of charge across the interface between the electrode and the electrolyte.
[0091] Cyclic stability is an important parameter of supercapacitors, representing the stability of supercapacitors. The capacitance retention rate of supercapacitors at a constant current of 100 μA can be obtained through multiple cycles of charge and discharge. Fig.19 As shown in FIG. 1 , at the end of 1000 charge-discharge cycles, the planar micro-supercapacitor assembled by the present invention maintains a capacitance retention rate of more than 95%; and from Fig.19 It can be seen that there is no obvious degradation in the shape of the GCD curve, which indicates that the supercapacitors fabricated by LIPD have excellent electrochemical stability.
[0092] In summary, the method of depositing a porous carbon film by femtosecond laser induced plasma proposed in the present invention can adjust the nonlinear effect of the laser and the substrate during the femtosecond laser scanning sandwich structure by adjusting the gap between the substrate and the polyimide film (for example, by introducing a gasket between the substrate and the polyimide film) on the basis of a sandwich structure of a glass substrate-polyimide precursor-carrier, so that the substrate is transformed from direct laser ablation to laser induced plasma ablation. This method not only avoids excessive laser ablation of the substrate to produce a flake structure that is easy to peel off, but also facilitates the formation of a microchannel with a glass-carbon recast layer on the substrate, promotes the close bonding of the glass surface and the porous carbon film, significantly improves the adhesion of the porous carbon film, and deposits a porous carbon film with super strong adhesion on the glass substrate. The present invention also studies and proves that the porous carbon film obtained by the above method has good hydrophilicity and conductivity, and can be used as a planar supercapacitor for energy storage.
[0093] The method of depositing porous carbon films by femtosecond laser-induced plasma and the method of assembling planar supercapacitors provided by the present invention successfully solve the shortcomings of laser-induced porous carbon films being difficult to transfer from polymer motherboards to other substrates with high quality and high efficiency. The prepared planar supercapacitors have good electrochemical properties and cycle stability, and have the advantages of being simple, controllable, highly repeatable, and capable of large-area preparation. The carbon-based devices prepared using this method have good stability and can effectively improve the robustness of supercapacitors during actual use. The method of femtosecond laser-induced plasma deposition has the advantages of high stability, repeatability, low loss, and operational sensitivity, and provides a simple and effective strategy for expanding the application scenarios of carbon-based electronic devices.
[0094] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. A method for laser induced plasma deposition of porous carbon film, characterized in that: The following steps are involved: The carrier, the polyimide film and the substrate are overlapped from bottom to top to form a sandwich structure; a gap is provided between the polyimide film and the substrate, and the width of the gap is 25 μm; The power of the femtosecond laser is adjusted to 500-700 mW; The pattern of the carbon electrode is designed in advance, the sandwich structure is fixed on a stage, and femtosecond laser scanning is performed according to the pattern of the carbon electrode to deposit the porous carbon film on the lower surface of the substrate; the scanning speed is 1-5 mm / s, the scanning interval is the same as the diameter of the femtosecond laser spot irradiated on the polyimide film, and the pattern of the porous carbon film corresponds to the shape of the carbon electrode.
2. The method for laser induced plasma deposition of porous carbon film according to claim 1, characterized in that: The gap is arranged in the following manner: two gaskets are provided between the polyimide film and the substrate, the two gaskets are symmetrically arranged on both sides of the to-be-deposited area of the substrate, and the thickness of the gaskets corresponds to the width of the gap.
3. The method for laser induced plasma deposition of porous carbon film according to claim 1, characterized in that: The laser scanning speed was 5 mm / s and the scanning interval was 10 μm.
4. The method for laser induced plasma deposition of porous carbon film according to claim 1, characterized in that: The substrate is a silicate glass substrate with a transmittance of 85%.
5. The method for laser induced plasma deposition of porous carbon film according to claim 1, characterized in that: The carbon electrodes are interdigitated electrodes, the effective length of the interdigitated electrodes is 7 mm, the width is 1 mm, and the number of the interdigitated electrodes is 5 pairs.
6. A method for assembling a planar micro supercapacitor, characterized in that: The porous carbon film is deposited on the lower surface of the substrate by the method described in any one of claims 1 to 6; an electrolyte and a current collector are prepared, and based on the electrolyte and the current collector, the planar micro supercapacitor is encapsulated to obtain the planar micro supercapacitor.
7. The method for assembling a planar micro supercapacitor according to claim 6, characterized in that: The electrolyte is H3PO4-PVA gel electrolyte.
8. The method for assembling a planar micro-supercapacitor according to claim 6, characterized in that: The current collector was assembled using flexible copper tape and conductive silver paste.